Social Network Applications and Free Online Mobile Numbers: Real Risk - Mehdi Dadkhah; Tole Sutikno; Shahaboddin Shamshirband (Institute of Advanced Engineering and Science, 2015)
Social network applications are being more widely used among users and new types of such applications are created by developers. Almost all users who use smart phones are users of such application. Major concern in these applications is privacy and security. We can name WhatsApp, Viber, Facebook, Telegram, Line, WeChat and Beetalk as the most popular applications. There are also websites which provide online numbers in order to receive SMS. The goal of this website is providing anonymous virtual phone number to protect users from spam. Also these sites provide different number from different countries and let people to can use them for different application. The services of these websites are divided into two groups: subscription services in which a unique number is assigned to the user by charging him/her and free services in which user can see the received messages of some online numbers without any registration.